Pengaruh Penambahan Aditif Diethanolamine (DEA) pada Ukuran Kristal Semikonduktor Copper Tin Oxide (CuSnO3) dengan Metode Sol-Gel - Karlina, Lilis; Sanjaya, Hary (Asian Journal of Science, Technology, Engineering, and Art, 2023)
This research involves the synthesis of Copper Tin Oxide (CuSnO3) using the sol-gel method. The synthesized CuSnO3 was characterized by X-Ray Difraction (XRD) to obtain the crystal size using the Debye-Scherrer equation. The crystal sizes obtained by adding 0 mL DEA and 2 mL DEA were 21.05 nm and 47.9 nm. There was an increase in crystal size with increasing DEA additive volume.